2009
DOI: 10.1194/jlr.m800594-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

FGF-1 induces expression of LXRα and production of 25-hydroxycholesterol to upregulate the apoE gene in rat astrocytes

Abstract: Fibroblast growth factor 1 (FGF-1) enhances apolipoprotein E (apoE) expression and apoE-HDL biogenesis in autocrine fashion in astrocytes (Ito, J., Y. Nagayasu, R. Lu, A. Kheirollah, M. Hayashi, and S. Yokoyama. Astrocytes produce and secrete FGF-1, which promotes the production of apoE-HDL in a manner of autocrine action. J. Lipid Res. 2005. 46: 679-686) associated with healing of brain injury (Tada,T., J-i. Ito, M. Asai, and S. Yokoyama. Fibroblast growth factor 1 is produced prior to apolipoprotein E in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Treatment of SH-SY5Y cells with inhibitors of mitogen activated kinase-kinase (MEK) or extracellular signal-regulated kinase-1 (ERK) potentiated the stimulatory effect of the HDAC inhibitor trichostatin A (TSA). This is in line with data on Cyp46a1 mRNA levels presented by Lu et al, in a rat astrocyte model, indicating increased mRNA levels following MEK inhibition, although there is high variability in these results [36]. In contrast treatment with the protein phosphatase inhibitor okadaic acid reduced the potency of the TSA effect.…”
Section: Cyp46a1supporting
confidence: 91%
“…Treatment of SH-SY5Y cells with inhibitors of mitogen activated kinase-kinase (MEK) or extracellular signal-regulated kinase-1 (ERK) potentiated the stimulatory effect of the HDAC inhibitor trichostatin A (TSA). This is in line with data on Cyp46a1 mRNA levels presented by Lu et al, in a rat astrocyte model, indicating increased mRNA levels following MEK inhibition, although there is high variability in these results [36]. In contrast treatment with the protein phosphatase inhibitor okadaic acid reduced the potency of the TSA effect.…”
Section: Cyp46a1supporting
confidence: 91%
“…Previous study reported that FGF1 could regulate biogenesis of APOE and HDL [Lu et al, 2009]. We were not able to determine the associations among the rs34011 variation and other clinical variables such as lipid levels because of the limited access to patients' data.…”
Section: American Journal Of Medical Genetics Part Bmentioning
confidence: 78%
“…FGF1 can affect the neuron survival in vulnerable brain areas [Thorns et al, 2001] and the level of FGF1 in CSF and serum was increased in AD patients [Mashayekhi et al, 2010]. In cultured rat astrocytes, FGF1 can regulate biogenesis of APOE and HDL which were highly associated with AD [Ito et al, 2007;Lu et al, 2009] and also can induce ATP release [Garre et al, 2010]. Due to the important role in the central nervous system, FGF1 has been reported to be associated with schizophrenia and intracranial aneurysm.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…There are hints that this effect of Cd may occur through epigenetic means. In this regard, we have observed that: 1) suppressed expression of ApoE by Cd is re-activated by 5-aza-2'-deoxycytidine (5-aza-dC), an effective DNA demethylating agent; and 2) possible involvement of liver X receptor α (LXRα, NR1H3) as a positive transcriptional factor (Laffitte et al, 2001;Lu et al, 2009). However, details of the molecular mechanisms precise events, such as a direct evidence for the Cd-induced DNA methylation, have not been resolved.…”
Section: Introductionmentioning
confidence: 99%